PREGNANT NUTRITION DATA REPORTING SYSTEM - Muhammad Adie Saputra; Muhammad Nur Ikhsanto; Sulistiyanto Sulistiyanto; Untoro Apsiswanto Untoro Apsiswanto (Journal of Technology and Data Science, 2022)
The system for reporting nutritional data on pregnant women at the Bantul Health Center currently uses the manual method, namely by handwriting or recording in a ledger, currently we are looking for data and making reports for each period experiencing difficulties. With the data processing system above, the work system carried out by the Bantul Health Center can be more effective and efficient in its performance when using a computerized system..